A comprehensive overview of daratumumab and carfilzomib and the recently approved daratumumab, carfilzomib and dexamethasone regimen in relapsed/refractory multiple myeloma. Issue 1 (2nd January 2021) - Richard, Shambavi; Jagannath, Sundar; Cho, Hearn Jay; Parekh, Samir; Madduri, Deepu; Richter, Joshua; Chari, Ajai
ABSTRACT: Introduction : Novel, effective regimens are needed in patients with relapsed and refractory myeloma (RRMM) who inevitably relapse after PI and IMID containing treatment. Areas covered : Pre-clinical data, early clinical and pivotal trials relevant to the development of the two backbone drugs of carfilzomib and daratumumab, and the two important recent trials, EQUULEUS and CANDOR leading to the FDA approval of the combination regimen of daratumumab, carfilzomib, and dexamethasone (DKd) for RRMM are detailed in this review. Expert opinion : EQUULEUS and CANDOR have established the efficacy of the DKd regimen in the landscape of bortezomib and lenalidomide refractory patients. The split dosing schedule of the first dose of daratumumab was approved by the FDA based on EQUULEUS, significantly improving patient convenience. Subcutaneous daratumumab is being evaluated in this combination to further improve tolerance and convenience. Further studies are needed to evaluate and optimally sequence the many effective and potent drugs available in RRMM.